Hubungan antara Literasi Gizi dengan Perilaku Makan Mahasiswa Aktif Program Studi Pendidikan Dokter Gigi - Saragih, Calysta Y. P.; Kapantow, Nova H.; Kawengian, Shirley E. S. (e-GiGi, 2025)
Abstract: Individual eating behaviors significantly influence nutritional balance. Students are vulnerable to nutritional issues due to unhealthy eating habits. Academic stress and a busy lifestyle often lead them to neglect less nutritious foods, potentially resulting in health problems. This study aimed to determine the relationship between nutrition literacy and eating behavior among active dentistry students at the Faculty of Medicine, Universitas Sam Ratulangi. This was an observational and analytical study using primary data collected through a Google Form questionnaire. The Spearman statistical test for the relationship between nutrition literacy and eating behavior showed a significant relationship in the enjoyment of food subscale (p=0.029), meanwhile, there were no significant relationships between nutrition literacy and eating behavior in the hunger (p=0.162), emotional overeating (p=0.934), food responsiveness (p=0.451), slowness in eating (p=0.133), emotional undereating (p=0.346), satiety responsiveness (p=0.481), and food fussiness (p=0.142) subscales. In conclusion, there is a relationship between nutrition literacy and eating behavior on the enjoyment food subscale of the AEBQ. Meanwhile, non-significant relationships were observed on hunger, emotional over-eating, food responsiveness, slowness in eating, emotional under-eating, satiety responsiveness, and food fussiness subscales. Keywords: nutrition literacy; eating behavior; dentistry students Abstrak: Keseimbangan gizi sangat dipengaruhi oleh perilaku makan individu. Mahasiswa rentan terhadap masalah gizi akibat kebiasaan makan tidak sehat. Stres akademik dan gaya hidup yang padat seringkali membuat mereka memilih makanan praktis kurang bergizi, yang berpotensi menimbulkan gangguan kesehatan. Penelitian ini bertujuan untuk mengetahui hubungan antara literasi gizi dengan perilaku makan mahasiswa aktif Pendidikan Dokter Gigi Fakultas Kedokteran Universitas Sam Ratulangi. Jenis penelitian ialah observasional analitik menggunakan data primer lewat kuesioner google form. Hasil uji Spearman terhadap hubungan antara literasi gizi dan perilaku makan menunjukkan hubungan bermakna pada subskala enjoyment food (p=0,029), namun tidak terdapat hubungan bermakna antara literasi gizi dan kebiasaan makan pada subskala hunger (p=0,162), emotional over-eating (p=0,934) food responsive (p=0,451), slowness in eating (p=0,133), emotional under-eating (p=0,346), satiety responsive (p=0,481), dan food fussiness (p=0,142). Simpulan penelitian ini ialah terdapat hubungan antara literasi gizi dan perilaku makan pada AEBQ subskala enjoyment food namun tidak terdapat hubungan bermakna pada subskala hunger, emotional over-eating, food responsive, slowness in eating, emotional under-eating, satiety responsive, dan food fussiness. Kata kunci: literasi gizi; perilaku makan; mahasiswa kedokteran gigi